Counteracting the Negative Effects of Copper Limitations Through the Biostimulatory Action of a Tropical Plant Extract in Grapevine Under Pedo-Climatic Constraints - Cirillo, Chiara; Arena, Carmen; Rouphael, Youssef; Caputo, Rosanna; Amitrano, Chiara; Petracca, Francesca; De Francesco, Sara; Vitale, Ermenegilda; Erbaggio, Arturo; Bonfante, Antonello; De Micco, Veronica (Frontiers in Environmental Science, 2021)
In southern Mediterranean areas, vineyards are facing the combination of increasing air temperature, drought and frequency of extreme events (e.g. heat waves) due to climate change. Since most of the berry growth and ripening phases occur during the aridity period, such environmental constraints are responsible for limitations in yield and berry quality. Within this scenario, to achieve vineyard sustainability, renewed approaches in vineyard management have been proposed and the use of plant biostimulants seems a prominent and environmental friendly practice. The aim of this study was to test four combinations of a tropical plant extract and conventional chemicals for disease control on morpho-anatomical, physiological, biochemical and berry quality in Vitis vinifera L. subsp. vinifera ‘Aglianico’. In particular, we aimed to evaluate the possibility to counteract the negative effects of the reductions in copper distribution, by applying the tropical plant extract enriched with: micronutrients, enzymes involved in the activation of natural defence, aminoacids and vitamins. The halved dose of Cu in combination with the tropical plant extract allowed maintaining a reduced vegetative vigor. In the second year of treatment, the addition of the plant extract significantly improved leaf gas exchanges and photochemistry as well as the synthesis of photosynthetic pigments. At berry level, the plant extract induced an increase in phenolics accompanied by a decrease in soluble sugars. The overall results showed that the expected differences in growth performance and productivity in vines are linked to different eco-physiological and structural properties induced by the various treatments. The tropical plant extract also primed plant defenses at the leaf and fruit levels, mainly due to modifications of some structural and biochemical traits respectively.